PENINGKATAN KAPASITAS KELEMBAGAAN NELAYAN UNTUK ADAPTASI TERHADAP PERUBAHAN IKLIM - denny hernawan; rita rahmawati; goris seran; muhammad luthfie (Universitas Djuanda, 2019)
This research is a qualitative descriptive study using data from the results of need assessment and the design of the initial phase model. Need assessment is needed to identify and map the symptoms of climate change in two research locations and how fishermen map existing institutions. The data are then used to formulate the initial model of institutional capacity for fishermen. The conclusions from the first year research are: (1) the understanding and knowledge of fishermen about climate change is relatively similar in two locations, namely empirical based on experience and pragmatic based on the characteristics of weather anomalies; (2) With a relatively low educational background, work ethic and a certain degree of rationality and efficiency for survival, fishermen in both research locations have a certain capacity to deal with climate change problems by building social relations, culture, community relations and their habitat; (3) fishermen make a relatively similar pattern of adaptation, namely changing professions temporarily, but still as a fisherman is the main job; (4) there are institutional arrangements in both locations consisting of government institutions (vertical institutions and regional offices), semi-official institutions, and fishermen groups or associations that are related to budget allocations and programs; (5) local institutions in both research locations have sought to increase their capacity through training, direct assistance or regional fisheries management programs so that fisheries resource management can be carried out sustainably; (6) general components that must exist in the initial institutional capacity. The model of the institutional improvement of fishermen consists of the development of human resources, business opportunities, improvement of resource management and environmental improvement carried out in an integrated and synergistic manner.Keywords: Capacity building, fishermen institutions, adaptation patterns, climate change, initial models